The sudden acclimatization of the Siganusrivulatus and the growth in different salinities - حسن, مراد; معينة بدران ,; كاترين منصور, (Latakia University Journal -Biological Sciences Series, 2022)
Our current study aimed to know the effect of reducing of salinities on the growth of Siganus rivulatus in different salinities.In addition: the sudden adaptation of fish in different salinities. the fish were caught from the coastal area adjacent to the Higher Institute of Marine Research, then they were transferred to the Institute into tank equipped with filters and oxygen pumps. Hydrological readings of the water were taken and fish weight measurements at the beginning of the experiment and every two weeks, as well as upon completion of the experiment ,the experiment continued for60 day. Sudden salinity: from sea water to fresh water, the fish lived for only an hour.they moved randomly, in addition to their imbalance in swimming, jumping above the surface and then swimming vertically towards the bottom of the aquarium, in addition to the extrusion of the eyes of the fish clearly . from sea water to 20‰ showed that the fish lived for a week. from sea water to 10‰ showed that the fish lived for a week. graduated salinity: The results showed that fish raised in 30‰ achieved the highest weight gain, which is 5.8 g. The fish raised in sea salinity also gave a weight gain of 5.2 g. The fish raised in 5‰ gave a weight gain of 4.3 g